2011
DOI: 10.1002/mds.24041
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease motor subtypes and mood

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 61 publications
7
110
0
2
Order By: Relevance
“…This association remained significant even after including possible confounders, such as duration of PD and levodopa therapy, to the second model. Patients with nontremor‐dominant types of PD are characterized as being more often depressed and having a more severe clinical picture, higher LEDD, and longer disease duration than patients with tremor‐dominant subtype (Burn et al., 2012). In a recent case‐control study in Italy investigating the relationship between clinical phenotype and the risk of developing dyskinesias, a significant negative association between tremor‐dominant phenotype as an initial PD manifestation and levodopa‐induced dyskinesia was established (Nicoletti et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This association remained significant even after including possible confounders, such as duration of PD and levodopa therapy, to the second model. Patients with nontremor‐dominant types of PD are characterized as being more often depressed and having a more severe clinical picture, higher LEDD, and longer disease duration than patients with tremor‐dominant subtype (Burn et al., 2012). In a recent case‐control study in Italy investigating the relationship between clinical phenotype and the risk of developing dyskinesias, a significant negative association between tremor‐dominant phenotype as an initial PD manifestation and levodopa‐induced dyskinesia was established (Nicoletti et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, when considering motor subtypes of PD, patients with the so-called postural instability gait difficulty (PIGD) subtype have been reported to experience depression more frequently and develop more rapid cognitive decline, compared with non-PIGD subtypes. 12,13 Because of the broad range of NMS, studies have employed a variety of screening tools and questionnaires to capture the frequency and severity of these symptoms. A significant advance has been the development and validation of a PD-specific screening questionnaire, the Nonmotor Symptom Questionnaire (NMSQuest), a 30-item questionnaire with screening questions for neuropsychiatric, sleep, genitourinary, gastrointestinal, sensory, and cognitive disturbances.…”
Section: Patients With Established Parkinson Disease (Pd) Experience mentioning
confidence: 99%
“…91 Studies have consistently found an association between anxiety, younger age of onset of PD, and presence of motor fluctuations. 5,85,92,93 In addition, there seems to be a link between wearing off of dopaminergic medications and increased anxiety. 48,93,94 etiology Anxiety in PD may be driven by the psychosocial stress of having the disease, 95 including social shame related to tremulousness and disability, being dependent on another person, fear of falling, and motor fluctuations.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…Akinetic rigid/PiGD motor subtype 25,[34][35][36] Motor fluctuations 5,85,92,93,104 Younger onset 87,104 Motor fluctuations 39,104 Younger disease onset 38,39,41 Right-sided motor asymmetry [41][42][43] Female sex 45 History of premorbid depression 45 Family history of depression 45 worse disability/poor cognition …”
Section: Risk Factorsmentioning
confidence: 99%